Architecture’s Awaking from Correlationist Slumber: On Transdisciplinarity and Disciplinary Specificity - Andrej Radman (Footprint)
Perception cannot be considered independently of the environment since it is defined as an evolved adaptive and constructive relation between the life-form and its milieu. Unfortunately, experimental psychology research has relied overwhelmingly on object perception, rather than environment perception, with the findings of the former providing the basis for understanding the latter.